“ISLAM” IN THE GLOBAL VILLAGE: POST-TSUNAMI DIALOG AND NEGOTIATION OF ACEH IDENTITY - Ibnu Mujib Mujib; Irwan Abdullah; Heru Nugroho (Al-Albab, 2013)
This paper highlights the perspective of dialog in the negotiation of Aceh identity. If observed, the context of the tsunami followed by the development of Aceh is not without impact at all on the Acehnese entity, but in fact it has triggered a strong clash especially between local identities and influences of global construction. Among the important things offered in this paper is an attempt to reproduce and create “public space” as a productive social capital, that is, a space that is expected to build an atmosphere of openness, egalitarianism, inclusivism of many diverse groups. Therefore, in responding to the wider variety of cultural plurality which penetrates through ethnic clusters, religions, political parties, and all forms of interests, it can be managed through the deliberations of dialog. Therefore, the “public space” that can serve to discuss, hold dialog, and even negotiate the clash of the Acehnese identity forms the modus operandi of the discussion of this article, especially in the context of the development of Aceh that is currently taking place. Keywords: Islam, locality, globality, public space, dialog, negotiation of identity, diversity of Islamic groups, the other.